1987
DOI: 10.3346/jkms.1987.2.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of ketoacidosis among Korean diabetic patients

Abstract: An epidemiological study on diabetic ketoacidosis (DKA) was done by analysis of 207 cases collected from the medical records of 6 major general hospitals in Seoul area during the period of 5 years between 1979 and 1984. There was female predominance in the occurrence of DKA (male/female ratio, 0.71) in spite of the male predominance in general prevalence of diabetes mellitus (1.80). This female predominance in DKA was most striking in the age group under 40. There was a significant seasonal variation in the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
2
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
0
8
2
1
Order By: Relevance
“…The proportion of adult DKAthat occurrs in previously undiagnosed patients ranges from 7. 1 to 27.5% (2,13,14). In our study, 22.7% of DKAepisodes (32 patients) occurred in patients without prior history of DM.Westphal (2) demonstrated that 9 of 37 patients with DKA-onset diabetes whowere followed for at least 12 months could be managed without insulin.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of adult DKAthat occurrs in previously undiagnosed patients ranges from 7. 1 to 27.5% (2,13,14). In our study, 22.7% of DKAepisodes (32 patients) occurred in patients without prior history of DM.Westphal (2) demonstrated that 9 of 37 patients with DKA-onset diabetes whowere followed for at least 12 months could be managed without insulin.…”
Section: Discussionmentioning
confidence: 99%
“…12 SAMJ Diabetic hyperglycaemic crisis is a major reason for high-care unit admissions, 1 with mortality rates of up to 30%. [2][3][4][5][6][7][8][9] It is characteristically classified as ketoacidotic or hyperosmolar. 10 Presentations with the combination of ketoacidosis and hyperosmolality are recognised, 6,7,[11][12][13][14][15][16] and have variably been described as ketoacidosis with hyperosmolality or hyperosmolar state with ketoacidosis, depending on whether ketoacidosis or hyperosmolality was considered dominant.…”
mentioning
confidence: 99%
“…We have seen an increase of severe hypoglycaemia in the spring and early summer in intensively treated children 16 . Diabetic ketoacidosis has been reported to occur more frequently in the winter 17 .…”
Section: Introductionmentioning
confidence: 99%